A 30-year follow-up study of patients with Melkersson–Rosenthal syndrome shows an association to inflammatory bowel disease. (17th February 2019) - Haaramo, Anu; Kolho, Kaija-Leena; Pitkäranta, Anne; Kanerva, Mervi
Abstract: Background: Melkersson–Rosenthal syndrome (MRS) is often classified under the term orofacial granulomatosis (OFG). A part of OFG patients eventually develop Crohn's disease (CD), but the relationship between MRS and CD is unknown. Goals: To evaluate the long-term outcomes of MRS patients, with specific interest in bowel-related symptoms. Study: This follow-up study consisted of adult patients with MRS – including the monosymptomatic form, cheilitis granulomatosa (CG) – who had participated in our earlier MRS study (diagnosed after 1995 in Helsinki University Hospital). A phone interview was conducted with 27 patients (77.1% of the patients from the earlier study) and included questions about orofacial symptoms, facial palsy, intestinal symptoms, concomitant illnesses, medications, possible food avoidances and family history. Stool samples were collected to measure faecal calprotectin, a surrogate marker for intestinal inflammation. Results: The median follow-up time from symptom onset was 30 years. Three (11.1%) patients had developed inflammatory bowel disease (IBD); one CG patient developed CD, and two MRS patients with facial palsy developed ulcerative colitis. In addition, several other patients reported intestinal symptoms, but the examination of faecal calprotectin did not indicate intestinal inflammation. Conclusions: There was a connection between MRS and IBD – not only CD but ulcerative colitis as well. Key message: Melkersson–Rosenthal syndrome (MRS) is a chronic condition often classified as a subtype of orofacial granulomatosis. Oral manifestations are common in MRS. We found a connection between MRS and inflammatory bowel disease, not only Crohn's disease but ulcerative colitis as well.